Impact of B-Scan Averaging on Spectralis Optical Coherence Tomography Image Quality before and after Cataract Surgery. (23rd May 2017) - Podkowinski, Dominika; Sharian Varnousfaderani, Ehsan; Simader, Christian; Bogunovic, Hrvoje; Philip, Ana-Maria; Gerendas, Bianca S.; Schmidt-Erfurth, Ursula; Waldstein, Sebastian M.
Abstract : Background and Objective. To determine optimal image averaging settings for Spectralis optical coherence tomography (OCT) in patients with and without cataract. Study Design/Material and Methods. In a prospective study, the eyes were imaged before and after cataract surgery using seven different image averaging settings. Image quality was quantitatively evaluated using signal-to-noise ratio, distinction between retinal layer image intensity distributions, and retinal layer segmentation performance. Measures were compared pre- and postoperatively across different degrees of averaging. Results. 13 eyes of 13 patients were included and 1092 layer boundaries analyzed. Preoperatively, increasing image averaging led to a logarithmic growth in all image quality measures up to 96 frames. Postoperatively, increasing averaging beyond 16 images resulted in a plateau without further benefits to image quality. Averaging 16 frames postoperatively provided comparable image quality to 96 frames preoperatively. Conclusion. In patients with clear media, averaging 16 images provided optimal signal quality. A further increase in averaging was only beneficial in the eyes with senile cataract. However, prolonged acquisition time and possible loss of details have to be taken into account.